Wages and the Movement of Factory Labor - Maclaurin, W. Rupert; Myers, Charles A. (Quarterly Journal of Economics, 1943)
Method of investigation, 242. — Movement between factories, 245. — Effect of inter-factory movement on wages, 248. — Persistence of wage differentials: factors affecting wage practices, 254; non-competitive hiring practices, 257. — Lack of competition among workers, 259; influence of family and friends, 260; absence of effective vocational guidance, 261; weakness of financial incentives, 261. — Summary, 262.